TEACHER STUDENTS TRAINING TO IMPLEMENT AR AND VR TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING - Rudnik, Yuliia (The Modern Higher Education Review, 2022)
The article is devoted to the problem of students’ training of the first educational level of pedagogical specialities (Primary and Preschool education) to the implementation of augmented and virtual reality technologies in foreign languages teaching. The notions of AR and VR technologies are clarified, and the necessity and specifics of the use of AR and VR technologies in foreign language teaching are explained. The article observes the use of AR and VR technologies in foreign language teaching as an essential part of the digital competence of the modern teacher. The choice of teaching methods, technologies, and tools in foreign language teaching is emphasized. Therefore, the professional training of pedagogical speciality students’(the first education level) significance is grounded. The depicted examples of such training are based on the working curriculum of the discipline “Mobile learning technology in foreign language teaching of preschool children”. This discipline is taught at Borys Grinchenko Kyiv University, and it is designed for the students of 012 Preschool education. This article focuses on the module “Mobile learning technology in foreign language teaching of preschool children,” which involves mastering AR technologies in teaching a foreign language at the preschool. The expected learning outcomes for the first education level pedagogical speciality students in terms of their professional training to use AR and VR technologies in foreign language teaching are discussed.